Macronutrient quality and colorectal cancer outcomes: evidence from the PLCO screening trial - Feng, Dazhan; Xiang, Ling; Wen, Ke; Xiao, Yi; Gu, Haitao; Peng, Linglong; Luo, Yuxiang; Wang, Yaxu; Liu, Dengliang; Zhou, Zhihang; Liu, Qian (Frontiers in Nutrition, 2026)
BackgroundNo previous study has assessed the relationship between macronutrient quality and colorectal cancer (CRC) incidence and mortality. Thus, to further explore the associations between macronutrient quality and CRC risk, we conducted a large prospective cohort study involving 101,709 people in the United States from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial.MethodsOur study population was derived from 154,887 adults aged 55 to 74 years who were recruited from 10 screening centers in the United States. The macronutrient quality index (MQI) was calculated based on dietary history questionnaire (DHQ). Cox regression analysis was utilized to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) of the associations between MQI and CRC incidence and mortality. We used subgroup analyses to identify potential effect modifiers. Sensitivity analysis was performed to ensure the study findings were robust.ResultsDuring the study period, 1,100 colorectal cancer (CRC) diagnoses and 314 CRC-related deaths were recorded. Higher adherence to the MQI was significantly associated with reduced CRC risk, demonstrating a 22% lower incidence (HR Q4 vs. Q1: 0.78; 95% CI: 0.65–0.93; p = 0.006 for trend) and 38% lower mortality (HR Q4 vs. Q1: 0.62; 95% CI: 0.44–0.86; p = 0.001 for trend) in the highest vs. lowest quartiles. These associations were robust across sensitivity analyses. Subsite-specific analyses revealed pronounced protective effects for distal colon cancer incidence (36% reduction; HR: 0.64; 95% CI: 0.43–0.96; p = 0.010 for trend) and mortality (56% reduction; HR: 0.44; 95% CI: 0.19–1.01; p = 0.037 for trend), with significant mortality reductions also observed for proximal colon cancer (34%; HR: 0.66; 95% CI: 0.44–1.00; p = 0.031 for trend).ConclusionOur findings suggest focusing on higher quality of macronutrient consumption may be an effective approach to reduce the risk of CRC in the US population.